Evaluation of a space-observed electric field structure for the ability to destabilize inhomogeneous energy-density-driven waves - I. V. Golovchanskaya; B. V. Kozelov; I. V. Mingalev; M. N. Melnik; A. A. Lubchich (Annales Geophysicae, 2014)
We examine the effectiveness of nonuniform, quasistatic, transverse electric fields that are often observed in the auroral region in destabilization of inhomogeneous energy-density-driven (IEDD) waves. Specifically, the IEDD dispersion relation of Ganguli et al. (1985a, b) is evaluated for an electric field structure observed by the FAST satellite in the auroral ionosphere at 1000 km altitude. The background field-aligned current, plasma density and ion composition are derived from FAST observations. Other input parameters adopted in the calculations are varied in pertinent ranges. Unstable solutions are obtained that indicate a variety of frequencies and perpendicular wavelengths. These can manifest as a broadband spectrum of IEDD waves.